La Paloma Trocal (Patagioenas speciosa) en Argentina - Bodrati, Alejandro; Cockle, Kristina; Segovia, José M.; Areta, Juan I.; Mérida, Emilse (Nuestras Aves, 2010)
Este artículo no cuenta con un resumen.